Analisis Kebijakan Jakarta Smart City Menuju Masyarakat Madani - Putri Zorayya Priyanti Noor; Suci Navasari; Muhammad Salman Jabbar Sangaji (Journal of Government Insight, 2021)
This paper aims to analyze and describe the development of the Jakarta Smart Cityter, including the advantages and disadvantages of the Jakarta Smart City which are associated with the use of information and communication technology to move towards civil society after more than four years. The method used in this research is literature review study. The results show that the implementation of Jakarta Smart City components such as smart mobility, smart government, smart economy, smart environment, smart living and smart people has been running well and is highly integrated with the use of information technology. From the research results, it can be concluded that the development of Jakarta Smart City which is now good, the relationship with the use of Information Technology is very close, while the disadvantage of Jakarta Smart City is that the development of information technology innovation is faster than the regulations, meaning that if there is the latest technological innovation it cannot be implemented immediately, must go through the budget regulation system. The structure of civil society in the city of Jakarta has been seen by the number of developments in large public areas and freedom from politics without any pressure. The government, the private sector and the public have collaborated in the development of a more innovative and transparent Jakarta.